Effect of cotton fabric properties on fiber release and marine biodegradation. Issue 11 (June 2022) - Kim, Seoyoun; Cho, Yoonkyung; Park, Chung Hee
The effects of cotton fabric structure and finishing on fiber emissions during washing and degradation were studied. Fabrics with different combinations of yarn count, weave structure, or weave density, and the fabrics dyed, water-repellent or peach skin finished were prepared. Significant fabric structural factors and resultant physical properties influencing the fiber release were statistically driven. The results showed that, on average, 16 wt% of the fibers was filtered through a washing machine, and the filtration rate increased when the discharged fibers were on average longer. It was found that the cotton fabric with a higher yarn count or weave density and more compact weave structure released a lesser amount of fibers and that their average length tended to be shorter. Compared to the untreated fabric, the fabric with peach skin finish released more fibers and the average fiber length was longer, whereas the fabric with water-repellent finish released fewer fibers that had a shorter length. It was demonstrated that cotton fiber emission could be reduced when the fabric had a larger weave parameter, low fuzziness, high abrasion resistance, and low water absorbency. Cotton fibers submerged in seawater exhibited a lower primary degradation than that of fibers buried in soil. In addition, the cotton fibers submerged in seawater maintained at 7°C exhibited a lower biodegradability than that of fibers submerged in seawater at 20°C. Moreover, in seawater, water-repellent fabric was biodegraded less than untreated fabric.